Using the Economic Value Added indicator to measure and analyze the economic institution’s financial performance in the context of the Corona pandemic - Case study: Biopharm Pharmaceutical Industry (2018 – 2023) - ali fedila, nassira (Journal of Research in Finance and Accounting, 2024)
The study's objective is to assess the economic institution's performance from a value creation standpoint using the Economic Value Added (EVA) indicator in order to ascertain how the COVID-19 pandemic affected the Biopharm Pharmaceutical Industry's financial performance between 2018 and 2023. We have determined that the pandemic had a detrimental effect on Biopharm's financial performance, leading to a decline in value in 2020, based on our measurement and analysis of the company's financial data. However, the company demonstrated the resilience of its operations and its capacity to handle health emergencies by making the correct decisions that allowed it to offer health goods at the right moment in 2021, generating positive additional value for all stakeholders.